Effectiveness and safety of Shenqi Fuzheng injection combined with platinum-based chemotherapy for treatment of advanced non-small cell lung cancer: a systematic review and meta-analysis - Qiao, Chenxi; Hu, Shuaihang; Wang, Dandan; Cao, Kangdi; Wang, Zhuo; Wang, Xinyan; Ma, Xiumei; Li, Zheng; Hou, Wei (Frontiers in Oncology, 2023)
Objective: To evaluate the efficacy and safety of Shenqi Fuzheng Injection (SFI) combined with platinum-based chemotherapy (PBC) for the treatment of advanced non-small cell lung cancer (NSCLC). Methods: Seven electronic databases, including CNKI and Wanfang, were comprehensively searched to screen randomized controlled trials (RCTs) until May 1, 2022. The quality of each trial was evaluated according to the Cochrane Handbook for Systematic Reviews of Interventions, and systematic reviews were conducted according to the PRISMA guidelines. Statistical analysis was performed using Review Manager 5.3, and the results were expressed as relative risk (RR) and 95% confidence interval (95% CI). The primary outcome measures were objective response rate (ORR) and disease control rate (DCR). The secondary outcome measures were quality of life and toxicity. Subgroup analysis was performed according to the number of days of SFI single-cycle treatment and combined PBC regimen. Results: A total of 44 RCTs involving 3475 patients were included in the study. The meta-analysis results showed that, compared with PBC alone, SFI combined with PBC significantly improved the ORR (RR = 1.27, 95% CI = 1.18–1.37, P < 0.00001), DCR (RR = 1.12, 95% CI = 1.08–1.15, P < 0.00001), and quality of life (RR = 1.41, 95% CI = 1.31–1.52, P < 0.00001). It also reduced chemotherapy-induced hemoglobin reduction (RR = 0.57, 95% CI = 0.48–0.67, P < 0.00001), leukopenia (RR = 0.61, 95% CI = 0.53–0.71, P < 0.00001), thrombocytopenia (RR = 0.62, 95% CI = 0.55–0.70, P < 0.00001), and simple bone marrow suppression (RR = 0.55, 95% CI = 0.41–0.73, P < 0.0001). Nausea and vomiting (RR = 0.63, 95% CI = 0.52–0.77, P < 0.00001), diarrhea (RR = 0.48, 95% CI = 0.37–0.64, P < 0.00001), and simple digestive tract reactions (RR = 0.63, 95% CI = 0.49–0.80, P = 0.0002) also decreased with the treatment of SFI. Conclusion: SFI combined with PBC for the treatment of advanced NSCLC improved the ORR, DCR, and quality of life, and reduced the incidence of myelosuppression and gastrointestinal adverse reactions. However, considering the limitations of existing evidence, further verification using high-quality RCTs is required.